High spatial resolution mapping of chemically-active self-assembled N-heterocyclic carbenes on Pt nanoparticles. (20th April 2016) - Levratovsky, Y.; Gross, E.
Abstract : The properties of many functional materials critically depend on the spatial distribution of surface active sites. In the case of solid catalysts, the geometric and electronic properties of different surface sites will directly impact their catalytic properties. However, the detection of catalytic sites at the single nanoparticle level cannot be easily achieved and most spectroscopic measurements are performed with ensemble-based measurements in which the reactivity is averaged over millions of nanoparticles. It is hereby demonstrated that chemically-functionalized N-heterocyclic carbene molecules can be attached to the surfaces of Pt nanoparticles and utilized as a model system for studying catalytic reactions on single metallic nanoparticles. The formation of a carbene self-assembled layer on the surface of a Pt nanoparticle and its stability under oxidizing conditions were investigated. IR nanospectroscopy measurements detected the chemical properties of surface-anchored molecules on single nanoparticles. A direct correlation was identified between IR nanospectroscopy measurements and macroscopic ATR-IR measurements. These results demonstrate that high spatial resolution mapping of the catalytic reactivity on single nanoparticles can be achieved with this approach.